The Social Negotiation of Group Prototype Ambiguity in Dynamic Organizational Contexts - Bartel, Caroline A.; Wiesenfeld, Batia M. (Academy of Management Review, 2013)
This article focuses on how the changing nature of work and working today elicits prototype ambiguity in groups—a shared perception among group members that the attributes, attitudes, and actions that define and describe the typical group member are unclear. We offer a functionalist account of prototype ambiguity identifying social contexts that reliably trigger ambiguity in group prototypes, group-level consequences of prototype ambiguity that motivate corrective action, and social negotiation processes by which group members adaptively resolve prototype ambiguity. We outline how group members' social negotiation efforts unfold in different but predictable ways (in response to specific triggers of prototype ambiguity) to yield emergent prototypes based on either central tendencies (as exemplified by the average group member) or ideals (as exemplified by the extraordinary group member). Concluding the article is a discussion of implications for research on social identity processes, group prototypes, and social hierarchies in organizations.